FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Jen Erika Marintan Sianturi (Pusat P2M Politeknik Negeri Batam, 2021)
This study aims to determine the effect of company size, working capital, efficiency, liquidity and leverage on company profitability. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The number of samples used was 104 companies using purposive sampling technique. This study uses secondary data with database collection techniques. The data analysis technique used panel data regression analysis. The results of the study found that company size, efficiency, liquidity and leverage have a positive and significant effect on company profitability, while working capital has a negative and insignificant effect on company profitability. Future research is expected to use samples other than the manufacturing sector and different measurements for the profitability variable in order to see the comparison of research results.